Pemanfaatan Limbah Kaca Sebagai Bahan Filler Untuk Pembuatan Bata Beton: Utilization of Waste Glass as Filler Material for Concrete Bricks - Riska Iga Saputri; Yoga C. V. Tethool; Rio O. Pramanagara (JISTECH: Journal of Information Science and Technology, 2023)
Concrete brick is a type of building element in the form of blocks made from the main ingredients of portland cement, water and aggregate used for wall (SNI 03-0349-1989). The concrete brick tested using glass powder added material is expected to produce high compressive strength and low water absorption. The method used is an experimental method by direct research at the Mining Laboratory of the University of Papua and processing the results of compressive strength and water absorption test data.The results of the compressive strength test for concrete bricks with the addition of glass powder with a large compressive strength value, namely in a 10% mixture of 36.256 kg/cm2, when viewed from the quality level based on SNI 03-0349-1989, concrete bricks with the addition of 10% glass powder are included in class IV category.The results of the calculation of water absorption obtained an average value of 0% glass powder, equal to 2.17%, 5% glass powder amounted to 5.08%, and 10% glass powder amounted to 4.92%, when viewed in a quality level based on SNI 03-0349-1989, concrete bricks with the addition of glass powder 0%, 5% and 10% fall into the class I category, namely 25%.The calculation results show that the cost of raw materials for concrete bricks with a mixture of 0% is Rp. 1,130,440, Concrete brick with a 5% mixture of Rp. 1,126,840, Concrete brick with a 10% mixture of Rp. 1,126,240. The results of the calculation of raw material costs show that using glass filler as a substitute for sand in the manufacture of concrete bricks is cheaper than normal concrete bricks.